(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of innovative pedagogical and information technologies in the process of personnel training, as well as the importance of foreign languages ​​in learning. The introduction of modern pedagogical approaches, interactive methods and information technologies in personnel training is of great importance in strengthening the knowledge and skills of students. At the same time, the possibilities of effective communication on a global scale and the training of competitive personnel through foreign languages ​​are discussed.